Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Camarena Velásquez, Claudia Cecilia (2018)
The objective of this research work is to propose a strategic plan to enter the Peruvian market for the Japanese corporation Fast Retailing. Directed by Tadashi Yanai, and under a SPA model, it has managed to position itself among the three best companies in the Fast Fashion Industry. With all this information, we started the plan analizing the external factors in order to identify those that may affect the company. The political factor is one of the most latent threats within the Peruvian situation which has been generated by the disagreement and conflict between the powers of the State, this crisis is not favorable for foreign investment. However, despite the political breakdown, the economy has managed to remain stable in recent years and the increase in consumption by the Peruvian population is one of the factors contributing to the economy. The main competitors within this industry in Peru are: Zara, H&M and Forever21, these companies already positioned and with a notable recognition by consumers. Through the analysis of Porter's 5 forces, we determined that the existing rivalry between these companies is high. The rapid access to information and new trends in clothing, generate the growth of a demand that seeks to meet their needs quickly and not much differentiation between products, companies are forced to implement strategies that allow them to get the attention of consumers. The proposal suggests the division of Uniqlo International into strategic units by regions, with the aim of better focusing the strategies and can be adapted to each market. The entry of Fast Retailing Corporation into the Peruvian market will be through the UEN Uniqlo International America. The implementation of a market penetration strategy, supported by the different suggested activities, will achieve the fulfillment of the established objectives in the short, medium and long term. Along with the strategy of differentiation, which is implemented from the parent company, Uniqlo America will be able to maintain low costs and offer differentiated products with high quality; these last factors are determinant for the purchase decision of Peruvian consumers, who are more informed and demanding at the time of making purchases. The existence of a wide market not yet explored by Fast Fashions and the growing demand for clothing consumption in trend are two of the factors that make Peru a country of opportunities and Uniqlo International America is prepared to take advantage of them.